Integrating sport psychology within a high-performance team: Potential stakeholders, micropolitics, and culture. Issue 1 (2nd January 2016) - McCalla, Trey; Fitzpatrick, Sean
ABSTRACT: High-performance teams of various sport science professionals working together to enhance performance are becoming commonplace in elite sport. Sport psychology professionals who desire to work within these groups, often referred to as high-performance teams, need to be prepared for the demands of a team-based performance enhancement setting. This article addresses the important factors to consider when integrating sport psychology within a high-performance team. The potential stakeholders are discussed, as are micropolitics and culture. The article closes with implications to assist in the ease of integrating sport psychology within a high-performance team.